2019
DOI: 10.1016/j.conbuildmat.2019.02.126
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of bio-based and recycled materials for indoor environmental comfort

Abstract: UK construction industry contributes 120 Mt of waste every year. Bio-based building materials may be a solution for this problem, as they combine re-use and recycling abilities together with hygroscopic characteristics, leading to buildings energy savings. For the first time, the dynamic response to hygrothermal changes of bio-based materials is examined in terms of Moisture Buffering Value (MBV), dry/ wet thermal conductivity, microstructure, density and latent heat through daily cycles. It is shown that MBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…However, these considerations should be verified: the performance of the composites widely varies depending on the complementary components (binders, additives) and the production method. Future As Collet [56] and Romano et al [72] reported, hygroscopicity properties widely affect the thermal behaviour of the composites and the control of the dynamic moisture changes. MBV values show the potential of bio-aggregates as hygric regulators [58].…”
Section: Water Absorption and Sorption/desorption Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…However, these considerations should be verified: the performance of the composites widely varies depending on the complementary components (binders, additives) and the production method. Future As Collet [56] and Romano et al [72] reported, hygroscopicity properties widely affect the thermal behaviour of the composites and the control of the dynamic moisture changes. MBV values show the potential of bio-aggregates as hygric regulators [58].…”
Section: Water Absorption and Sorption/desorption Propertiesmentioning
confidence: 98%
“…Furthermore, the measurement method (opening and closing of the climatic chamber) might have determined an error that has to be taken into consideration. As Romano et al [72] reported, the difference between the biowastes might depend on a micro-capillary network formation that is created during water molecules sorption/desorption. Table 7 reported MBV values [g/(m 2 •% RH)] and the classification provided by Rode et al [49]: Negligible: MBV = 0.0-0.2; Limited: MBV = 0.2-0.5; Moderate: MBV = 0.5-1.0; Good: MBV = 1.0-2.0; Excellent: MBV ≥ 2.0.…”
Section: Water Absorption and Sorption/desorption Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, nonrenewable materials such as expanded polystyrene (EPS) contribute to an immediate increase in global warming potential (GWP), for example through their energy‐intensive production process (Pittau et al, 2019). Bio‐based insulation materials can help mitigate depletion of nonrenewable resources and also contribute to the passive control of indoor air conditions (temperature and humidity) via hygroscopicity (Romano et al, 2019; Torres‐Rivas et al, 2018). They are non‐irritant, rendering them more user‐friendly, and being biodegradable lead to less pollution when disposed of (Lawrence, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous research articles have demonstrated the prospective use of industrial wastes for different construction applications [33,46,47]. As alternative material studies are now clearly a priority for decreasing energy consumption and solving waste management problem, several studies have shown that the use of such wastes in the development of unfired earth building materials can meet this environmental challenge [33,48,49]. Therefore, researchers have made considerable efforts to partially substitute soil or clay with specific agro and non-agro waste materials to produce sustainable unfired earth blocks.…”
Section: Introductionmentioning
confidence: 99%